Computational structural studies of SGLT2-related polypharmacy - Aled Lloyd; Karl Austin-Muttitt; Jonathan G.L. Mullins (PLoS ONE, 2025)
Introduction Sodium Glucose Cotransporter 2 (SGLT2) is the main active transport protein involved in sodium and glucose reabsorption in the kidney. SGLT2 inhibitors (SGLT2i) are widely recommended for patients with diabetes, heart failure and chronic kidney disease (CKD). Many multimorbid patients are prescribed these compounds, raising questions about polypharmacy. We have performed a computational drug repurposing screen to identify other licensed drugs capable of binding at or near the SGLT2i active site aiming to identify compounds that could either compete with SGLT2i or inhibit sodium and glucose transport. Methods The library of BNF listed compounds was obtained from NCBI PubChem. D-I-TASSER was used to generate monomeric structural models, and MODELLER was used to incorporate MAP-17 and empagliflozin from a reference structure (PDB 7VSI). CHARM-GUI was used to insert the protein into a membrane. The structural model was refined in a 5 nanosecond GROMACS equilibration. Docking studies using PLANTS were performed and compounds interacting with key protein residues were identified. CHARM-GUI was used to prepare membrane- and ligand-bound systems to run in GROMACS using GPUs in Google Colab. 10 nanosecond simulations were undertaken (300 Kelvin and 1 bar) to discriminate between binding and non-binding events. Results The SGLT2-MAP17 structure was obtained in the inward-open conformation, showing good agreement with published structures. Existing SGLT2i (empagliflozin, dapagliflozin, canagliflozin, ertugliflozin) all feature in the top 1% of docked compounds in the repurposing screen. 17 compounds were investigated by MD, with all of them remaining bound to the protein in simulation. Ceftriaxone, tobramycin, clindamycin, fluvastatin, atorvastatin and ticagrelor were among the compounds with potentially significant interactions. Discussion It is not clear whether the stable ligand interactions identified here would result in inhibition of sodium and glucose transport, or if the interactions could provide competitive inhibition for SGLT2i compounds currently used. The compounds identified are not presently recognised as interacting with SGLT2i, nor are they associated with any adverse effects suggesting inhibition of the protein. This study is limited by considering only the protein-ligand interaction and not wider pharmacokinetic or pharmacodynamic factors. Conclusion The indication of interactions with several compounds likely to be prescribed alongside SGLT2 inhibitors, such as antibiotics, statins, and antiplatelet agents, warrants further investigation of the potential for polypharmacological complications.